"Determining a Health-promoting Lifestyle among Afghan Immigrants Women in Iran". (September 2020) - Ahmadi, Zahra; Amini, Leila; Haghani, Hamid
Background: Health-promoting lifestyle is an effective strategy for maintaining and controlling health, especially in immigrant women as a vulnerable group. Regarding this, the present study was conducted to determine the health promoting lifestyle and its associated factors in Afghan migrant women in Iran. Method: This was a population based cross-sectional study in which 255 Afghan women of reproductive age. The study population was selected using the continuous sampling method from all Afghan women who referred to health centers of southwest of Tehran in 2018. The data were collected through the socio-demographic and Health Promoting Lifestyle Profile-II (HPLP-II) questionnaire. Results: The total HPLP-II mean score of women was (124.05 ± 17.28). The lowest score was related to physical activity dimension (14.70 ± 3.78) and the highest score was related to spiritual growth (24.56 ± 5.06). Although some factors such as age, duration of education, income level, ability to speak Persian, education level of husband, and number of children significantly related factors to participant's lifestyle ( P <.05), but multiple regression model showed that income level and ability to speak Persian are final statistically related factors to Afghan women health promoting lifestyle in Iran. Conclusion: Familiarization of the individual with the Persian language and the promotion of employment status should be considered due to the low socio-economic level and the fact that most women participating in the study are housewives.